2006
DOI: 10.1037/0735-7044.120.4.952
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain structures specifically activated by conditioned taste aversion.

Abstract: This study investigates which forebrain structures show Fos protein expression during conditioned taste aversion (CTA) acquisition and whether Fos expression depends on the aversion strength. A novel taste paired with an intraperitoneal injection of a low dose of the malaise-inducing agent lithium chloride (LiCl) induced a weak CTA, whereas associating this novel taste with a high dose of LiCl induced a strong CTA. Increasing the strength of the gastric malaise alone enhanced Fos expression in central, basal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Interestingly, consistent with previous studies showing that LiCl injection did not induce the expression of the activation marker c-fos in the GC (16)(17)(18), the malaise itself does not induce significant changes in the correlations between saccharin and quinine patterns (P CS-Ctrl/US-Ctrl ϭ In the following test days (TD1 and TD2), a preference test for distilled water (Wat.) over saccharin (Sac.)…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, consistent with previous studies showing that LiCl injection did not induce the expression of the activation marker c-fos in the GC (16)(17)(18), the malaise itself does not induce significant changes in the correlations between saccharin and quinine patterns (P CS-Ctrl/US-Ctrl ϭ In the following test days (TD1 and TD2), a preference test for distilled water (Wat.) over saccharin (Sac.)…”
Section: Resultssupporting
confidence: 75%
“…We took advantage of the unique features of the central taste system where changes in internal body states, such as satiety (20) or visceral malaise (16,19) have a direct influence on primary GC neuronal responses.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the analysis of c-Fos IR in the CNA revealed that the density of Fos-positive nuclear profiles increases following the LiCl-only injection, but the magnitude of this increase is greater when the blockade of the NOP occurs. This is in concert with previous studies showing that LiCl elevates c-Fos IR in the CNA (43), and the c-Fos response depends on the strength of the aversive stimulus (11). Additionally, the level of c-Fos IR in the amygdala is memorydependent following the induction of a CTA (43).…”
Section: Discussionsupporting
confidence: 72%
“…Two hours later rats received ip injections of either 0.4 M LiCl or physiological saline at 1.0 ml/100 g. The pattern and magnitude of c-Fos expression has been found to be the same following administration of 0.15 M or 0.4 M NaCl (Ferreira, Ferry, Meurisse, & Lévy, 2006). Therefore, 0.15 M saline was used in the control condition of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining structures innervated by the PBN (GT, BNST, IC) have been examined to a much lesser degree typically in experiments in which lithium was administered as a control condition (e.g., LiCl-only) and therefore was not the focus of the investigation. These studies suggest (1) little involvement of the IC (Billig, Yates, & Rinaman, 2001;Ferreira, Ferry, Meurisse, & Lévy, 2006) and (2) that the medial BNST may express c-Fos following lithium treatment in the ferret (Billig et al, 2001); to our knowledge the GT has not been investigated. The purpose of this study is to confirm these prior findings and to explore additional structures implicated in LiCl-induced viscerosensory information processing.…”
Section: Introductionmentioning
confidence: 97%